Precalculus mathematics : algebra and trigonometry - Bryant, Steven J.; Saltz, Daniel (California : Goodyear Publishing Company, Inc., 1980)
The purpose of this book is two-fold: first, to present the algebraic techniques that are needed for calculus, and second, to present topics that are traditionally covered in college algebra and trigonometry.
1. Basic properties -- 2. Functions and graphs -- 3. Exponential and logarithmic functions -- 4. Right triangle trigonometry -- 5. The trigonometric functions -- 6. Further applications of trigonometry -- 7. Systems and matrices -- 8. Properties of polynomials -- 9. Sequences, sums, and series -- 10. Probability, counting, and induction.
Includes index.
Keywords: TRIGONOMETRY -- CALCULUS